Immigration Research in the U.S.A.: Some Approaches to the Problems of the Second Generation - Kodrič, Majda (Two Homelands, 1990)
This paper comprises a survey of some fundamental publications by American immigrations researchers on the problem of “the second generation”. Included particularly are works on the position of the second generation in the Italian and Slavic ethnic communities. The rudimentary treatments of this theme among Slovene emigrants to USA are also considered. For practical reasons the time range of the surveyed American publications is somewhat limited. They reach only to the first half of the 1980s expect for some witch only a few paragraphs deal with this problem. The considered works investigate the problems of the second generation within various disciplines, such as psychology, pedagogics, historiography, social linguistic and ethnology. On the same issue of the position of the second generation within the Slovene National Benefit Society, some newspaper source was used. Less ... Among the problems of the second generation, that is, the immediate descendants of immigrants, the question of school education - especially the relationship between the family as the bearer of ethnic tradition and the American public school as the mediator of American behaviour patterns - is of central signifinance. The paper is focused on this theme, but also considers other problems of the second generation. The conflict within children of immigrants, between adaptation to the American milieu and fidelity to the ethnic tradition - from a psychological point of view - is the research theme of Irvin L. Child, who distinguishes an indifferent response to such conditions and notes the joint apperennce of both tendencies, with one or other usually prevailing. In the Italian and Slavic ethnic groups, the latter response was most frequent. Different value systems among immigrants of various ethnic origins have influenced behaviour of the second generation, of course. As for the initial experiences of the children of Slovene and Italian immigrants in American schools, the ascertainment by Nives Sulič that the ethnic tradition is rejected to the benefit of the American manner of life, is similar to that of Leonard Covello. The latter also ascertains that with the further growth of the second generation, ethnic identity comes to prevail and there is simultaneous alienation from school. Such conclusions were also made by Salvatore J. La Gumina, who considered the Italian ethnic community, and by John Bodnar considering the Slavic. Following habits from the old homelands, the Italian and Slavic immigrants tended also in the USA to concentrate exclusively on family upbringing of children in order to help maintain the family. Dislike for school was also a consequence of the denationalizational policy of the Austro-Hungarian educational system, of the negligence of the values of the peasant masses in Italy and of the assimilation tendencies in American schools. Covello and La Gumina point out the possibility of inadequate valuing of ethnic traditions in American public schools. Bodnar and Mark Stolarik observe the inevitable contradiction between the spiritual aims of Slavic upbringing and the materialistic orientation of the American school. They stress the connection between cultivating ethnic consciousness and preserving the Catholic religion through the role of parish schools. They also point o u t the disinterest in educating children through the primary degree, which Bodnar connects with limited possibilities for social and economic mobility among immigrant children. Ewa Morawska stresses the mutual interdependence of this lack of mobility and of ethnic values as a source of frustration. I t obstructed tendencies towards advancement and acculturation which actually existed, as can be seen from the two paragraphs on the second generation in the works by Morawska and John J. Bukowczyk. Therefore, Bodnar’s approach is evidently incomplete, as he underestimates such aspirations. This limits his interpretation of socialistic thinking as simultaneously arguing for public education and for the cultivating of ethnic consciousness, a tendency which Karel D. Bicha notices among the Czech, and which both N. Sulič and the author of this contribution note among the Slovene immigrants. Preserving ethnic identity, along with accepting the inevitable acculturation, is also identified as important by Joshua A. Fishman and Vladimir C. Nahirny, in whose opinions the degree of preservation is not as important as the quality.